(3GdUHM GdoefHi Yf MjKjI GdeJfHjs - (3jhSa GdHOjYj GdOeTbj GdMdHjs; (3CHhGdWjH CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeYQha H` CHj GdWjH GdoeJfHj,J (B354 (3g` s
(3ChdgG (B:s
(3aUeeJ GdYRe Ydi PcQ eNJUQ jMJhj Ydi PcQ CHj GdWjH GdeJfHj hCNHGQg, hjTJed Ydi fHP ef bdGFOg hCTYGQg s
(3BNQgG (B:s
(3aEfg de jHYO aGVd hdG TGYQ ef CHfGA GdTgHGA hdG ef ZjQgG Gdebjejf ajgG, EdG hbO cJH JbQjXkG heOM Hg LfGH GdehdigPG OYGA jTed cd EfSGf ajLH Cf jfWb Hg cd dSGfhGdMeO ddg Ydi GdJeGe hGdceGd, fLR GdcJGHI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B63 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B13 s
Keywords: (3GdCOHs